Factors stimulating the hatching of resting eggs and their contribution to the composition of cladoceran assemblages in tropical temporary lagoons - Guimarães, Wesley Luiz [UNESP]; Panarelli, Eliana Aparecida; Dos Santos, Natan Guilherme [UNESP]; Castilho-Noll, Maria Stela Maioli [UNESP] (FapUNIFESP (SciELO), 2024)
Aim: We aimed to verify the contribution of cladocerans’ resting eggs to the active communities of temporary lagoons and, through an experiment, identify which conditions induce high hatching rates. Methods: Cladocera assemblages were sampled in four temporary lagoons in the Turvo River floodplain (20° 22’S and 49° 16’W), in the northwest region of São Paulo State, Brazil. Sediment samples were taken during the dry season from a depth of 5 cm, using a 4.5 cm diameter corer. Plankton samples were taken from the water column before and after the dry season. For the hatching test, two treatments were performed 1. Natural condition – without light and temperature control; 2. Controlled condition – with controlled photoperiod and temperature. Temperature, pH, conductivity, dissolved oxygen and hatching of resting eggs were monitored for two weeks. The influence of the parameters on hatching in both treatments was evaluated using Hierarchical Partition Analysis. Results: Hatching of resting eggs was higher in the Controlled condition than in the Natural one. Thirty percent of species observed in the active community after flooding hatched in the laboratory test. Conductivity, pH, and dissolved oxygen were positively correlated to the hatching of some species, e.g., Ephemeroporus hybridus, Leydigiops ornata, Notoalona sculpta and Ilyocryptus spinifer. The first species to hatch were those living associated with macrophytes and at low depths. Conclusions: Our results show that stable temperature and photoperiod with similar light and dark hours stimulate greater hatching of Cladocera resting eggs. Variables such as pH, conductivity and dissolved oxygen were also correlated with the hatching of some species. We observed that the first contributions to activating the community after drought came from hatching of species usually associated with macrophytes and low depth conditions.
Fatores que estimulam a eclosão de ovos de resistência e a sua contribuição para a composição das assembleias de cladóceros em lagoas temporárias tropicais
Keywords: dormant community; ephippium; experiment; flood plain; sediment